486 DISCORDANT CIRCADIAN RHYTHM AND NEUROPATHOLOGY IN ALZHEIMER'S DISEASE TRANSGENIC MICE. (1st January 2006) - Levy, E. J.; Miller, C. A.; Miller, J.; Zhou, L.
Abstract : Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive decline in cognitive function, dementia, and eventual mortality. Neuropathological features of AD include β-amyloid (Aβ) plaque deposition and neurofibrillary tangles (NFTs) in the cerebral cortex, as well as dysfunction of synaptic terminals and decreased synaptic number. An early behavioral feature of AD is the disruption of sleep cycles. The relative timing of the neuropathological changes and the symptomatic cognitive decline is unknown. In this study we examine the relationship between the earliest microanatomical and cognitive manifestations of AD by determining the temporal relationship, if any, between the appearance of neuropathology and the onset of circadian rhythm abnormalities in 3-month-old transgenic (Tgx3) mice (Oddo, 2003). Locomotion of 3-month AD and wild-type (WT) Tgx3 mice was observed for 1 month and recorded as interruptions of a matrix of infrared beams in constant darkness. The interruptions were plotted as a function of time and analyzed for 24-hour rhythm power. Three-month AD and WT mice were anesthetized and preserved with intracardiac perfusion of 10% formaldehyde. Coronal sections were stained with hematoxylin and eosin; immunohistochemical and fluorescent stains, including Gallyas silver, Thioflavin S, anti-Aβ 1-42, and immunoperoxidase were used to detect NFTs and Aβ. Stains for Aβ 1-42 and NFTs were negative. However, preliminary analysis indicates a 5.45-fold decrease in the power of the 24-hour circadian rhythm in AD mice compared to WT. These preliminary findings suggest that symptoms of behavioral decline characteristic of AD may precede the neuropathological changes.